HISTOPATHOLOGY OF WHITE RAT SPLEEN INDUCED BY THE APPLICATION OF MIMOSIN FROM LEUCAENA LEAF SIMPLISIA - Luh Gede Tasya Pradnya Prastistha; I Ketut Berata; Nyoman Sadra Dharmawan; Ni Nyoman Werdi Susari; Ni Luh Eka Setiasih; Luh Made Sudimartini (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
The Leucaena leucocephala is often used as an alternative feed for cattle. However, the utilization of leucaena leaves as cattle feed needs to be restricted because leucaena contains an anti-nutritional substance called mimosine. This study aimed to evaluate the impact of mimosine exposure from the leucaena plant on the spleen of white rats. The research used twenty male Wistar strain white rats aged 2 months weighing 300–350 grams, with spleen tissue as the sample. The treatment was divided into four different groups, including a negative control group, a positive control group given standard mimosine, and two groups exposed to leucaena leaf simplisia at different doses for 14 days via gavage. On the 15th day, the rats were euthanized for spleen extraction to prepare histopathological slides stained with hematoxylin-eosin. The results of histopathological examination, including congestion, bleeding, and inflammation, were analyzed using non-parametric Kruskal-Wallis and Mann-Whitney tests. Oral administration of mimosine from leucaena leaf simplisia to the spleen of white rats showed histopathological changes such as congestion, bleeding, and inflammation. The Kruskal-Wallis test revealed significant changes in congestion, bleeding, and inflammation. The Mann-Whitney test between rats given mimosine from leucaena leaf simplisia at doses of 50 mg/head/day and 150 mg/head/day showed a significant effect on inflammatory histopathological changes. Based on the research results, it can be concluded that there were histopathological changes, including congestion, bleeding, and inflammation due to mimosine administration from leucaena leaf simplisia compared to controls, and there was an influence of different doses of mimosine from leucaena leaf simplisia between doses of 50 mg/head/day and 150 mg/head/day, especially on inflammatory lesions. It is recommended for future research to further investigate the administration of mimosine from leucaena leaf simplisia over a longer period with larger doses.